PELATIHAN MEDIA PEMBELAJARAN KIMIA MENGGUNAKAN SOFTWARE KINGDRAW DAN PENGENALAN REAGEN ALAMI UNTUK ANALISIS DI SMK BHAKTI KENCANA - rismiarti, zuri; Indra, Asep Iin Nur; Rohayati, Rohayati (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2024)
Organic chemistry learning materials about writing the structure of organic chemistry molecules, pictures of simple practical tools are obstacles in learning chemistry. This is due to the lack of technology-based skills to make it easier to write this material in teaching materials. One of the superior teaching methods that needs to be taken into consideration is the provision of multimedia-based teaching materials and supporting facilities. It is hoped that the availability of technological facilities and multimedia teaching materials will make it easier for students to understand the material/lessons. Strengthening the ability to master multimedia-based teaching materials is still hampered by the lack of skills in making KingDraw software teaching materials. Apart from that, the partner has 3 chemical laboratories but does not have a comprehensive insight into natural reagents for chemical analysis that can be used for chemistry practicum. Therefore, in this community service program scheme, the proposer provides several solutions and programs to provide development training. learning media/teaching materials through KingDraw software and introduction to natural reagents for chemical analysis at SMK Bhakti Kencana Cimahi. Strengthening students' competencies by applying the application of natural ingredients as reagents for chemical analysis can help with laboratory practicums in chemical analysis subjects. Thus, this community service activity can be useful for schools to improve the quality of teachers in updating knowledge based on KingDraw software technology to develop teaching materials.